Mayo Test Drive: Reliability and construct validity of the Stricker Learning Span and Symbols Test on a self‐administered web‐based testing platform optimized for smartphone. (31st December 2021) - Karstens, Aimee J; Stricker, John L; Geske, Jennifer; Hassenstab, Jason; Fields, Julie A.; Mielke, Michelle M.; Stricker, Nikki H.
Abstract: Background: Mayo Test Drive (MTD): Test Development through Rapid Iteration, Validation and Expansion, is a web‐based platform for remote self‐administered assessment for novel (Stricker Learning Span; SLS) and open access (Symbols Test) cognitive measures. The SLS is a computer adaptive word‐list memory test that matches test difficulty to user performance. The SLS visually presents words for learning exposures and 4‐choice recognition to test encoding across 5 trials. Symbols is a measure of processing speed being used in many remote assessment studies and typically employs a burst design; in MTD participants complete 4 trials (12‐items each). We examine validity and reliability of the SLS and Symbols via MTD. Method: Forty‐five women enrolled in an ongoing study of the Sex‐Specific Effects of Endocrine Disruption on Aging and Alzheimer's Disease were recruited via email or phone. The Auditory Verbal Learning Test (AVLT) and Digit Symbol Coding (Coding), administered in person within the past 2 years (Mean = 11 months), were used to establish construct validity. Participants (91.3% White, Mean age=66.2 years, Mean education=15.3 years) were emailed a link to complete the SLS and Symbols remotely at their convenience on their own device and emailed to repeat testing after approximately 1 week. Pearson correlations ( n= 45) and 2‐way mixed intraclass correlation coefficients (ICC; n= 42) determined construct validity and test‐retest reliability, respectively. Significance was set at p <.05. Result: Across all test sessions initiated, 97% were successfully completed. Most were completed at home (92.6%; vs. at work or in a public space), and device type varied (48% smartphone, 2% tablet, 50% PC). Median session completion time was 15 minutes. SLS learning scores (max span, total correct trials 1‐5) significantly correlated with AVLT 1‐5 total ( r 's .37‐.39) and AVLT Trial 5 ( r 's .51‐.52). SLS delay significantly correlated with AVLT delay ( r =0.45) and recognition ( r= 0.61). Symbols time‐based scores averaged across trials were significantly correlated with Coding ( r's= ‐.48‐(‐).50). Test‐retest reliabilities across 2 sessions were high for SLS (ICC's=.80‐.88) and Symbols (ICC's=.81‐.82). Conclusion: SLS and Symbols are valid and reliable self‐administered remote tests in older females. Future work will examine effects of Alzheimer's disease neuroimaging biomarkers and risk factors on these tests.